Avoidance: From Basic Science to Psychopathology - Richard J. Servatius (Frontiers Research Topics, 2016)
Coping has a myriad of facets: knowledge concerning the circumstances of threats to emotional and physical well being, the ability to meet immediate needs to mitigate, the potential for recurrence, the ability to apply efforts and resources to manage recurrence, and the complex assessment of competing motivations and changing circumstances. Successful coping is measured in the efficiency of efforts in balance with the degree of threat and likelihood of future occurrence. As one means of coping, avoidance encompass thoughts and efforts toward prevention of future aversive experiences and events. Anxiety disorders exemplify an extreme bias toward avoidance. A diathesis learning model focuses research efforts on individual vulnerabilities to acquire and express avoidance, the neurobiology of avoidance learning and its attendant circuitry. A fundamental understanding of avoidance through a diathesis learning model offers will facilitate the development of effective treatment protocols in alleviating anxiety disorders.